2013
DOI: 10.1016/j.jcrs.2013.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of povidone–iodine 1.0%, 5.0%, and 10.0% irrigation combined with topical levofloxacin 0.3% as preoperative prophylaxis in cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 23 publications
4
33
1
Order By: Relevance
“…The preset study and the Wykoff et al study 19 support the use of a larger volume and higher concentrations of povidone-iodine. This is in accordance with other studies that used the conjunctival bacterial load as a surrogate marker for the risk for postoperative endophthalmitis [13][14][15] and found a greater reduction in bacterial colonies when higher concentrations or larger volumes of povidone-iodine were used. [13][14][15] In the present study, the risk for postoperative endophthalmitis after cataract surgery declined during the study period.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The preset study and the Wykoff et al study 19 support the use of a larger volume and higher concentrations of povidone-iodine. This is in accordance with other studies that used the conjunctival bacterial load as a surrogate marker for the risk for postoperative endophthalmitis [13][14][15] and found a greater reduction in bacterial colonies when higher concentrations or larger volumes of povidone-iodine were used. [13][14][15] In the present study, the risk for postoperative endophthalmitis after cataract surgery declined during the study period.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with other studies that used the conjunctival bacterial load as a surrogate marker for the risk for postoperative endophthalmitis [13][14][15] and found a greater reduction in bacterial colonies when higher concentrations or larger volumes of povidone-iodine were used. [13][14][15] In the present study, the risk for postoperative endophthalmitis after cataract surgery declined during the study period. Taban et al 20 published a systematic review of English-language articles and found rates of postoperative endophthalmitis of 0.087% in the 1990s and 0.265% from 2000 to 2003.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with studies that have used reduced conjunctival bacterial load as a surrogate marker for reduced post-operative endophthalmitis. [37][38][39] Antibiotics in the irrigating solution Sobaci et …”
Section: Peri-operative Measuresmentioning
confidence: 99%